3D printing of porous Si2N2O ceramics based on strengthened green bodies fabricated via strong colloidal gel. (5th January 2020) - Jin, Haize; Yang, Zhihua; Cai, Delong; Jia, Dechang; Zhou, Yu
Abstract: A convenient direct ink writing porous ceramic preparation strategy incorporating green body strengthening measure was provided. Different hydrogen bond interactions between particles in polar and nonpolar solvents have been successfully applied to regulate the rheological properties of 3D printing ink. Inks with different (NH4 )H2 PO4 content were systematically optimized, which exhibited acceptable ambient stability and superior printing behavior. The phosphoric acid generated by decomposition of (NH4 )H2 PO4 reacts with silica or oxide layer of silicon nitride to form Si–O–P binder by a pretreatment at low temperature to strengthen the green body. The compressive strength of green body fabricated by ink with 0.2  g/mL (NH4 )H2 PO4 was increased by 415%. The Si2 N2 O single wall frame structure parts with a compressive strength of 3.33 ± 0.14 MPa under a frame density of 1.14 ± 0.05 g/cm 3 were fabricated. The dielectric constants of the developed ceramic parts range from 3.57 to 4.21. A systematic study of design and preparation of ink and quantization of molding parameters provide a reference for in-situ reinforced the ceramic green body of silica, silicon nitride and their composites, as well as fabrication of their corresponding highly porous ceramic components based on the direct ink writing. Graphical abstract: Image 1 Highlights: A strategy for direct ink writing of high-strength Si2 N2 O green bodies as well as their ceramic components was provided. The rheological properties of inks were regulated by the different hydrogen bond interactions between particles in C10 H22 O5 and H2 O. The phosphorus elements introduced by (NH4 )H2 PO4 aqueous solution were evenly distributed in green body and ceramic part. The compressive strength of Si2 N2 O green body was increased up to 415% due to the strengthening of Si–O–P binder.